2017
DOI: 10.1080/0284186x.2017.1337925
|View full text |Cite
|
Sign up to set email alerts
|

Residential traffic noise exposure and vestibular schwannoma – a Danish case–control study

Abstract: The present study does not suggest an association between residential traffic noise and VS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…For example, this bias is commonly observed in the vestibular schwannoma literature, in which persons will report significant exposures related to hearing (eg, occupational noise exposure) after learning that they have developed a tumor on their hearing nerve; however, prior objective, population-based studies that do not rely on surveys demonstrate no such association. [18][19][20] Considering these methodological limitations of prior research, we believe the data from the current study do not support the assertion that pregnancy increases the risk of developing otosclerosis nor does it contribute to worsening hearing loss.…”
Section: Discussioncontrasting
confidence: 87%
“…For example, this bias is commonly observed in the vestibular schwannoma literature, in which persons will report significant exposures related to hearing (eg, occupational noise exposure) after learning that they have developed a tumor on their hearing nerve; however, prior objective, population-based studies that do not rely on surveys demonstrate no such association. [18][19][20] Considering these methodological limitations of prior research, we believe the data from the current study do not support the assertion that pregnancy increases the risk of developing otosclerosis nor does it contribute to worsening hearing loss.…”
Section: Discussioncontrasting
confidence: 87%
“…Although several survey-based studies have reported an association between noise exposure and the development of sporadic VS 19,20 or between cell phone use and sporadic VS, 21 several robust population-based case-control studies have refuted these claims. [22][23][24] The apparent discrepancy is most likely accounted for by the susceptibility of the aforementioned survey-based studies to recall bias, where patients who have been diagnosed with a tumor on their hearing nerve are Several incidence rates were reported in this study; however, for reasons exhaustively described in the original study, the rate of 3.3 per 100,000 personyears likely represents the most accurate estimate reported based on completeness of data. 10 reasonably more likely to note exposures related to hearing.…”
Section: Discussionmentioning
confidence: 73%
“…Although several survey-based studies have reported an association between noise exposure and the development of sporadic VS 19,20 or between cell phone use and sporadic VS, 21 several robust population-based case-control studies have refuted these claims. 22-24 The apparent discrepancy is most likely accounted for by the susceptibility of the aforementioned survey-based studies to recall bias, where patients who have been diagnosed with a tumor on their hearing nerve are reasonably more likely to note exposures related to hearing. Similarly, patients with significant cell phone use may be more sensitive to asymmetrical hearing loss and consequently undergo workup.…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies are prospective, randomized or blinded but mostly case–control studies. Of importance, no association has been found between occupation, traffic/loud noise nor the use of mobile phones and tumor occurrence 3437. Lastly, exposure to radiation is known to cause neoplasms including intracranial 3841…”
Section: Discussionmentioning
confidence: 99%